(untitled) - Clough, Ray W; Penzien, Joseph (Berkeley, Calif., 2007)
5 parts (28 chapters): Single degree of freedom systems; multi degree of freedom systems; distributed parameter systems; random vibrations; earthquake engineering
Keywords: Earthquake engineering -- Structural dynamics; Kỹ thuật địa chấn -- Động lực kết cấu